2014
DOI: 10.3177/jnsv.60.291
|View full text |Cite
|
Sign up to set email alerts
|

S-Equol Enantioselectively Activates cAMP-Protein Kinase A Signaling and Reduces Alloxan-Induced Cell Death in INS-1 Pancreatic ^|^beta;-Cells

Abstract: Summary S-Equol is enantioselectively produced from the isoflavone daidzein by gut microflora and is absorbed by the body. An increase of pancreatic b-cell death is directly associated with defects in insulin secretion and an increased risk of type 2 diabetes mellitus. In the present study, we demonstrate that only the S-enantiomer has suppressive effects against alloxan-induced oxidative stress in INS-1 pancreatic b-cells. S-Equol reduced alloxan-induced cell death in a dose-dependent manner, whereas R-equol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
0
20
0
2
Order By: Relevance
“…The sole member of this genus, Adlercreutzia equolifaciens, is an equol-producing bacterial strain. Though little is currently known about this species, previous work has indicated that the production of equol by gut microbiota can have beneficial metabolic impacts, including improved leptin/BMI profiles (35) and antioxidant activity (36), and protection from b-cell death (37). In addition, comparison of BBc and BBdp rats demonstrated an alteration in the composition of microbiota, many of which are taxonomically related, in the BBdp rat.…”
Section: Discussionmentioning
confidence: 99%
“…The sole member of this genus, Adlercreutzia equolifaciens, is an equol-producing bacterial strain. Though little is currently known about this species, previous work has indicated that the production of equol by gut microbiota can have beneficial metabolic impacts, including improved leptin/BMI profiles (35) and antioxidant activity (36), and protection from b-cell death (37). In addition, comparison of BBc and BBdp rats demonstrated an alteration in the composition of microbiota, many of which are taxonomically related, in the BBdp rat.…”
Section: Discussionmentioning
confidence: 99%
“…Medium with mogrol was replaced to fresh medium every 2 days. The cells were then incubated in fresh medium containing 5% AlamarBlue (Trek Diagnostic Systems, Cleveland, OH, USA) for 4 h in the dark prior to the measurement of fluorescence, as described previously [30]. …”
Section: Methodsmentioning
confidence: 99%
“…3T3-L1 cells grown on a 48-well plate to confluence were transfected with 0.2 μg of p4xCRE-TATA-Luc [30] and 0.1 μg of pGL4.74[hRluc/TK] using 0.75 μL of HilyMax reagent (Dojindo, Kumamoto, Japan) for 48 h. On day 0, the medium was exchanged to normal culture medium or fresh differentiation medium and the cells were incubated in the presence of 20 μM mogrol or 1 mM AICAR for 30 min. Then, cells were stimulated with insulin, DEX, and IBMX for 24 h. Luciferase activities were determined as described previously [31].…”
Section: Methodsmentioning
confidence: 99%
“…The cells were transfected with double‐strand siRNAs for AR (AR#1 sense: 5′‐GACUCAGCUGCCCCAUCCA(dTdT)‐3′ and AR#2 sense 5′‐ ACCAUGCAGAAUACAAAU(dTdT)‐3′) or control double‐strand siRNA (Sigma, SIC001) as described previously [Harada et al, ; Mitani et al, ]. Briefly, the cells were transfected using 10 nM siRNA and 0.5 μl of Lipofectamine RNAiMAX (Life Technologies, Gaithersburg, MD), incubated for 24 h, and then incubated in the presence or absence of AR ligand for 72 h. Cell viability was determined using AlamarBlue Dye (TREK Diagnostics Systems, Cleveland, OH) and survival rate was determined as described previously [Horiuchi et al, ].…”
Section: Methodsmentioning
confidence: 99%